Tapp in the treatment of irreducible and inguinoscrotal hernia - Ivantsok, V.; Bondariev, R.; Bondarieva, O. (Journal of Education, Health and Sport, 2022)
Laparoscopic surgery is known to be technically difficult to perform for irreducible and inguinoscrotal hernias. The aim of the work is to conduct a comparative analysis of early postoperative complications in the surgical treatment of irreducible and inguinoscrotal hernias using the modified laparoscopic and classic TAPP techniques. Comparative analysis of the local early postoperative complications in 49 male patients who were surgically treated for irreducible and/or inguinoscrotal hernias was carried out. The patients were divided into 2 groups according to the technique of hernioplasty: the first group (n = 19) - surgical treatment was performed by the classical hernioplasty, described in the literature, TAPP technique; the second group (n = 20) - surgical treatment included a modified laparoscopic TAPP technique. Only 1 (5.3%) patient in group 1 (p = 0.079) who had experienced bleeding during surgery. Post-operative subcutaneous emphysema was common in 5.3% in group 1 and 5.0% in group 2 (p = 0.490), inguinal hematoma in 5.3% and 5.0% (p = 0.490), scrotal hematoma in 10.5% and 0% (p = 0.445), inguinal paresthesia 5.3% and 5.0% (p = 0.490), inguinal seroma 5.3% and 5.0% (p = 0.490), scrotal seroma 26.3% and 0% (p = 0.047), orchiepididymitis 5.3% and 0% (p = 0.079) respectively. The modified technique of transabdominal preperitoneal repair of irreducible and inguinoscrotal hernia provides low-trauma fractures of surgery, which reduced the incidence of local intra- and postoperative complications.